2022
DOI: 10.1038/s41598-022-16984-9
|View full text |Cite|
|
Sign up to set email alerts
|

A multicenter study to compare the effectiveness of the inpatient post acute care program versus traditional rehabilitation for stroke survivors

Abstract: There is insufficient evidence to prove the effect of the Post-acute Care (PAC) program on post-stroke recovery. This study aimed to determine the effectiveness of the PAC versus traditional inpatient rehabilitation (non-PAC) for middle- and old-aged stroke survivors. This multicenter cohort study enrolled 334 stroke patients admitted for post-stroke rehabilitation. The outcome variables included the Barthel Index (BI), Functional Oral Intake Scale (FOIS), Mini Nutritional Assessment-Short Form (MNA-SF), EuroQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The PAC-CVD program is considered a more economical and favorable recovery strategy than traditional rehabilitation [12,33]. Chen et al recently reported that within the first year after stroke rehabilitation, the NHI cost was higher in the non-PAC group (USD 3785 per person) than in the PAC group (USD 3480 per person) [13].…”
Section: Discussionmentioning
confidence: 99%
“…The PAC-CVD program is considered a more economical and favorable recovery strategy than traditional rehabilitation [12,33]. Chen et al recently reported that within the first year after stroke rehabilitation, the NHI cost was higher in the non-PAC group (USD 3785 per person) than in the PAC group (USD 3480 per person) [13].…”
Section: Discussionmentioning
confidence: 99%
“…The studies that applied the MNA-SF to stroke patients were all carried out in Far Eastern Countries, apart from one from Italy [ 18 , 34 , 35 , 49 , 50 , 51 , 52 , 62 , 63 ], as shown in Table 1 . In most studies, patients (suffering from AIS or AHS) were recruited by rehabilitation facilities.…”
Section: Nutritional Screening Toolsmentioning
confidence: 99%
“…Upon admission, the MNA-SF score is significantly related to cognitive impairment ( Table 2 ) and independence in ADL [ 35 , 49 , 51 , 52 ], but not quality of life [ 35 ]. The MNA-SF showed better improvement when energy intake upon admission was higher [ 52 ], and when a post-acute care program was compared to a traditional inpatient rehabilitation approach [ 18 ]. As for clinical outcomes, in a rehabilitation setting, the MNA-SF has been associated with functional independence at discharge but not with the discharge destination [ 50 , 51 ].…”
Section: Nutritional Screening Toolsmentioning
confidence: 99%
“…13 In a multicenter study, an intensive rehabilitation program initiated within the first month after stroke resulted in greater improvement in ADL, nutrition, cognition, and shorter LOS than a traditional program initiated later. 14 It is widely known that recovery is relatively quick in the first month following a stroke and then slows down 3 to 6 months later. 15 Hence, the first month, which is considered as a window of opportunity, should be included in the rehabilitation pe-riod.…”
Section: Discussionmentioning
confidence: 99%